Ukrainian products: problems and perspectives - Maevska, Catalina (My University, 2014)
Food industry has always been one of the most important sectors, especially in Ukraine. Харчова промисловість завжди була однією з найбільш важливих галузей, особливо в Україні.
Keywords: ukrainian products; food industry; українські продукти; харчова промисловість; украинские продукты; пищевая промышленность